2016
DOI: 10.7759/cureus.913
|View full text |Cite
|
Sign up to set email alerts
|

Novel and Conservative Approaches Towards Effective Management of Plantar Fasciitis

Abstract: We assessed the effectiveness of the different treatments for plantar fasciitis (PF) based on the changes in functional outcomes. A systematic literature search was carried out and studies from 2010 to 2016 were included in this review. The databases from Google Scholar, PubMed and Cochrane were used for the various treatment modalities of plantar fasciitis. The objectives measured included visual analog scale (VAS), Roles and Maudsley scale, foot function index (FFI), plantar fascia thickness and American Ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…[ 82 ] The FFI is the most widely used foot-specific self-reporting measure[ 83 ] and is a commonly used outcome measure in patients with PF. [ 22 , 32 , 41 ] The FFI has been shown to be valid, reliable and sensitive to change in various populations with a variety of foot and ankle disorders. [ 83 , 84 ] Subscale scores range from 0% to 100%, with higher scores indicating lower levels of function and poorer foot health-related quality of life.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 82 ] The FFI is the most widely used foot-specific self-reporting measure[ 83 ] and is a commonly used outcome measure in patients with PF. [ 22 , 32 , 41 ] The FFI has been shown to be valid, reliable and sensitive to change in various populations with a variety of foot and ankle disorders. [ 83 , 84 ] Subscale scores range from 0% to 100%, with higher scores indicating lower levels of function and poorer foot health-related quality of life.…”
Section: Methodsmentioning
confidence: 99%
“…For cases of persistent PF, physicians often recommend corticosteroid injections;[ 8 , 31 ] however, while corticosteroid injections may be useful for managing PF symptoms at short-term, long-term outcomes appear to be lacking. [ 23 , 32 , 33 ] Moreover, steroid injections have been linked with plantar fat pad atrophy, calcaneal osteomyelitis, plantar fascia weakening and rupture. [ 34 – 36 ] Platelet rich plasma treatment has also been found to be effective for PF;[ 37 ] nevertheless, platelet rich plasma injections are considered controversial, expensive and are not normally covered by insurance plans.…”
Section: Introductionmentioning
confidence: 99%
“…Three reviews without meta-analysis reported superiority of PRP treatment. [64][65][66] On the opposite, two recent meta-analysis of nine RCTs failed to confirm those data. 67 68 Tsikopoulos et al 67 showed that corticosteroid injections are more effective in pain relief in the short term, whereas Yang et al 68 ► Most common term referred to a cluster of products including: autologous conditioned plasma, platelet-enriched plasma, platelet-rich concentrate, autogenous platelet gel, platelet releasate, platelet rich in growth factors and others.…”
Section: Plantar Fasciitismentioning
confidence: 99%
“…However, around 10% of patients seemed not to respond positively. 64 Therefore, PRP injections into the plantar fascia, with or without ultrasound guidance, have been recently introduced as an alternative therapy. Recent systematic reviews, comparing corticosteroid versus PRP injections, reported controversial results.…”
Section: Plantar Fasciitismentioning
confidence: 99%
“…[ 3 ] It has been estimated that about 90% of patients with PF get relief through conservative management alone. [ 4 ] Although there are many treatment modalities, there is no consensus for a definitive nonsurgical method for symptom relief in individuals with PF. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%